2022
DOI: 10.4314/ejhs.v32i4.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chitosan-PEG Nanoparticles Based on Channa striata Protein Hydrolyzate on Decreasing Diabetes Mellitus in Diabetic Rats

Abstract: BACKGROUND: Channa striata has several good nutrients, including 70% protein, 20% albumin, complete amino acids, zinc, selenium, and iron. However, no study has investigated the chitosan-PEG nanoparticles based on Channa striata protein hydrolyzate. This study’s purpose was to determine the role of 10% Channa striata protein hydrolyzate, chitosan-PEG 4000 nanoparticles, and chitosan- PEG 6000 nanoparticles in reducing diabetes mellitus in diabetic rats.METHOD: A randomized pretest-posttest control group design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The average weight of the pancreas in the study was still within the normal range. Saraswati et al (2022) in his research found that nanochitosan can accelerate the proliferation of cells in the islets of Langerhans in the pancreas, such as alpha cells and beta cells. Nanochitosan is also known to increase insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The average weight of the pancreas in the study was still within the normal range. Saraswati et al (2022) in his research found that nanochitosan can accelerate the proliferation of cells in the islets of Langerhans in the pancreas, such as alpha cells and beta cells. Nanochitosan is also known to increase insulin secretion.…”
Section: Resultsmentioning
confidence: 99%